PEMANFAATAN JAHE PUTIH TERHADAP MUAL MUNTAH IBU HAMIL TRIMESTER I - Ani T Prianti; Rahmawati Rahmawati (Pusat Riset dan Inovasi Nasional, 2022)
Hyperemesis Gravidarum is vomiting that occurs until 20 weeks of gestation. Vomiting occurs so intense that everything that is eaten and drunk is vomited up, affecting the general condition of the mother. The management of mild hyperemesis gravidarum is very important, namely by giving ginger extract drink. Giving ginger drink for 1 week with the rule of drinking a third of a teaspoon of powdered ginger extract brewed using warm water and drunk three times per day. The purpose of this study was to determine the effect of drinking ginger extract on mild Hyperemesis Gravidarum in pregnant women. This outreach method is by providing an explanation to the community before the intervention in the form of ginger extract drinks and after the experiment in the form of giving ginger extract drinks. The number of samples in this study were 15 respondents who were pregnant women with mild hyperemesis gravidarum in Manyampa Hamlet. The leaflets were used. Furthermore, From the results of this counseling, it is hoped that the general public, especially health workers, can socialize the use of ginger extract drinks for pregnant women with Mild Hyperemesis Gravidarum. The target of this counseling is to reduce nausea and vomiting in pregnant women, especially pregnant women who experience nausea and vomiting in order to improve the quality and quality of services for pregnant women.